Material Ramah Lingkungan untuk Interior Rumah Tinggal - Dila Hendrassukma (Humaniora, 2011)
Housing is one of the biggest contributors in polluting the ozone layer and consuming the natural resources in making one. Home interior takes part in the over-produced material used for covering the interior elements, such as floor, wall, ceiling, and furniture. The article conducting is to study the green aspect of building materials to find alternative material to beautify the house that is not harming the earth. The result is options of eco material to be used in the making of greener home interior. It is materials that can be renewed, recycled, and low in embodied energy. Materials used in home interior have impact to the natures. Thus, awareness in choosing the right material to decorate the house is very important.